METRIC CHARACTERISTIC OF ANATOMICAL PREPARATIONS OF THE MATURE MALE CORPUS CALLOSUM - Boiagina, O.D.; Kostilenko, Yu.P.; Linnyk, A.S.; Yakovcova, N.Yu.; Molodchyy, R.A. (World of Medicine and Biology, 2017)
At present, it is not possible to perform a comparative analysis of the metric indices of the median sections of corpus callosum obtained by measuring its MRI images and the ones made using its anatomical preparations as the object of study. The reason for that is mainly the fact that the only statistically reliable data concerning the basic metric parameters of the corpus callosum we have, was obtained on the basis of measuring its MRI images. Therefore, we set the goal to digitalize the same parameters of the corpus callosum in its postmortem state on a quantitatively comparable sample of its anatomical preparations and, as a result of comparing the two data, to determine the statistical difference between them in order to approximate their true value. In the course of study we used photographs of the medial surfaces of cerebral hemispheres (after a two-week fixation in a 10% neutral formalin solution) of 25 men aged 36 to 60 years who died for reasons not related to CNS pathology. In some cases, we resorted to obtaining isolated whole preparations of the corpus callosum by excising it in the sagittal plane in the form of a plate approximately 2 mm thick. Later they were subjected to dehydration in alcohols with transition to acetone for subsequent plastination in epoxy resin, in accordance with the technique developed by us. After complete polymerization, the resulting preparations were polished and stained with 1% solution of methylene blue. Morphometric analysis of the sagittal profile of corpus callosum was carried out according to its photographs using the computer program Adobe Photoshop CS6 Extended. As a result of the study, a large individual variety of the corpus callosum shape was revealed, which is phenotypically created due to the different combinatorics of the shape and dimensions of its individual parts. Drawing a parallel between two different samples of images of the corpus callosum sagittal profile, we must pay attention to the fact that compared with MR tomograms, corpus callosum contour lines in the photographs of anatomical preparations are more distinct, realizing the details that are not available for magnetic resonance imaging. This fact is not so significant for the visual evaluation of the corpus callosum shape, but in metric analysis it should affect the accuracy of the results. Indeed, such differences with a pronounced individual variability were recorded for all linear and planimetric parameters. As a result of the study, there was no correlation between the age of men in the mature period of life and the size of the corpus callosum. There is a significant individual diversity of its combinatorial form and metric parameters. This can correlate with certain psychophysiological properties of people and give the prospect of further studying of this problem with the help of magnetic resonance imaging.